Novel Techniques of Single-CarrierFrequency-Domain Equalization for Optical Wireless Communications. (4th October 2010) - Acolatse, Kodzovi; Bar-Ness, Yeheskel; Wilson, Sarah Kate
Abstract : We investigate the use of single carrier frequency domain equalization (SCFDE) over a diffuse optical wireless (DOW) communications. Recently orthogonal frequency division multiplexing (OFDM) has been applied to DOW communications. However, due to high peak-to-average power ratio (PAPR), the performance of OFDM can severely be affected by the nonlinear characteristics of light emitting diodes (LED). To avoid a PAPR problem, we present in this paper a modified form of SCFDE for DOW communications. We propose three different ways of using SCFDE with DOW communications and show that they exhibit lower PAPR and provide better bit-error rate (BER) performance in the presence of the LED nonlinearity.